Intention to have no children and its relation to mental health: a case study of personality and coping traits of married couples, registering at Bangrak District Office - Wattanavitukul, Pichaya; Roomruangwong, Chutima (Chulalongkorn Medical Journal, 2022)
Background: Modern families tend to have fewer children, planning to have no children has seen more and more. There are pieces of evidence that many families planned to have no children even the family’s economic status has improved. Objectives: To examine the prevalence of intention to have no children among those who come to get marriage registration at Bangrak District Office, Bangkok Metropolis, and association between intention to have no children and personality and coping. Methods: The cross-sectional descriptive study was conducted in males and females who come to get marriage registration at Bangrak District Office, Bangkok Metropolis. The data were collected by questionnaires including demographic data questionnaire, the Maudsley Personality Inventory (MPI), and Coping Questionnaire. The characteristics of the subjects were presented as frequency and percentage. Inferential statistics were analyzed by Chi-square, t - test, and logistic regression. Results: There were 380 subjects (male 186, female 194) with a mean age of 33.1 ± 6.0 years. The prevalence of intention to have no children was found 13.7%. Personality-Scale E was found significantly associated with intention to have no children, in which the subjects with introverted personality tend to have higher intention to have no children than those with extraverted personality. Also, those with the intention to have no children have significantly lower in problem focus coping (dimension - seek to belong), while having significantly higher in avoidance coping, avoidance coping (dimension - keep to self), and avoidance coping (dimension - behavioral disengagement). Conclusion: Personality and coping plays an important role in influencing individuals’ intention to have or have no children.